Kemampuan Metakognitif Siswa dalam Menyelesaikan Soal Cerita Sistem Persamaan Linier Tiga Variabel - Nita Fatma Fauziah; Edi Purwanto (FKIP Universitas Mataram, 2026)
One of the important elements in successful problem solving is metacognition. One of themathematical problems is expressed in the form of a Three Variable Linear Equation System storyproblem. This study is a type of qualitative research that aims to describe students' metacognitiveabilities as reviewed from the components and indicators of the Metacognitive AwarenessInventory (MAI). The main instrument in this study is the researcher himself, while the supportinginstruments are the Three Variable Linear Equation System story problem test and interviewguidelines. The subject in this study was 1 (one) grade XI student who was selected based on theresults of solving the Three Variable Linear Equation System story problem and consideration ofthe mathematics teacher's recommendations. The results of the study indicate that SB'smetacognitive ability in solving the Three Variable Linear Equation System story problem includescomponents, namely (1) declarative knowledge, (2) procedural knowledge, (3) conditionalknowledge, (4) planning, (5) information management strategies, (6) comprehension monitoring,(7) debugging strategies and evaluation.